2009
DOI: 10.1016/j.vetpar.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte entry into the CNS of Leishmania chagasi naturally infected dogs

Abstract: In dogs, there is an association of chronic visceral leishmaniasis with neurological symptoms, and very few publications have investigated whether these neurological manifestations correlate with specific alterations in brain. A total of 42 mixed-breed adult dogs were selected from the Veterinary Hospital of UNESP-Araçatuba and the Control Zoonosis Center in Araçatuba, São Paulo State, Brazil, which is an endemic area for visceral leishmaniasis. Animals presenting positive ELISA and/or positive parasitological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 54 publications
7
35
0
1
Order By: Relevance
“…Analysis of the CNS of dogs infected with L . infantum revealed the presence of anti- Leishmania antibodies in cerebrospinal fluid (CSF) [6, 8, 14, 16, 18, 20] and of L . infantum DNA in the brain [13, 2022] and CSF [11].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the CNS of dogs infected with L . infantum revealed the presence of anti- Leishmania antibodies in cerebrospinal fluid (CSF) [6, 8, 14, 16, 18, 20] and of L . infantum DNA in the brain [13, 2022] and CSF [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the most common CNS finding is infiltration of inflammatory cells during VL infection of dogs [33], there are reports of presence of amastigotes in both choroid plexus [37] and meninges [49] (which was confirmed via immunohistochemistry in experimental infection [48]). It is also reported to be not uncommon to see ocular changes with canine VL [30].…”
Section: Leishmania Infectionmentioning
confidence: 87%
“…Reports of neuro-inflammation associated with natural and experimental VL infection [1,33], as well as the presence of Immunoglobulin in aqueous humor and cerebrospinal fluid (CSF) [15] suggest a disruption of the blood-brain barrier (BBB), and the bloodcerebrospinal fluid barrier underlies the CNS manifestation of disease. The BBB functions to exclude microscopic objects and large hydrophilic molecules, and is achieved by endothelial cell specializations including tight junctions between cells, a specialized basal lamina surrounding the vessels in the brain, and an ensheathment of the vessels made of astrocytic endfeet [11].…”
Section: Disruption Of the Blood Brain Barriermentioning
confidence: 99%
“…Other studies, despite the observation of histopathological alterations in the CNS of dogs during visceral leishmaniasis, failed to verify the presence of Leishmania amastigotes [11, 19, 20, 2325]. Some authors explain these contradictory findings by the chronicity of the disease, arguing that the presence of Leishmania in the CNS has generally been demonstrated in dogs with an earlier infection, either because of delayed diagnosis or by the choice of treatment for the infected dogs, as in two studies in the Mediterranean region [11, 24]. In fact, here we observed that animals that presented amastigote forms in the CNS had clinical signs such as cachexia and the presence of skin lesions, observed in the chronic phase.…”
Section: Discussionmentioning
confidence: 99%